2013
DOI: 10.1002/cam4.112
|View full text |Cite
|
Sign up to set email alerts
|

BAY 87‐2243, a highly potent and selective inhibitor of hypoxia‐induced gene activation has antitumor activities by inhibition of mitochondrial complex I

Abstract: The activation of the transcription factor hypoxia-inducible factor-1 (HIF-1) plays an essential role in tumor development, tumor progression, and resistance to chemo- and radiotherapy. In order to identify compounds targeting the HIF pathway, a small molecule library was screened using a luciferase-driven HIF-1 reporter cell line under hypoxia. The high-throughput screening led to the identification of a class of aminoalkyl-substituted compounds that inhibited hypoxia-induced HIF-1 target gene expression in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
184
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(192 citation statements)
references
References 39 publications
(44 reference statements)
7
184
0
1
Order By: Relevance
“…Under conditions of glucose depletion that favor mitochondrial ATP generation in cancer cells as energy source, BAY 87-2243 inhibited cell proliferation in the nanomolar range (27). BAY 87-2243 interference with mitochondrial function resulted in reduced hypoxia-induced HIF-1 activity in tumors and prompted exploration of its use with radiation as a therapeutic approach to overcome chemo-and radiotherapy resistance of hypoxic tumors (45).…”
Section: Hif Inhibitorsmentioning
confidence: 99%
“…Under conditions of glucose depletion that favor mitochondrial ATP generation in cancer cells as energy source, BAY 87-2243 inhibited cell proliferation in the nanomolar range (27). BAY 87-2243 interference with mitochondrial function resulted in reduced hypoxia-induced HIF-1 activity in tumors and prompted exploration of its use with radiation as a therapeutic approach to overcome chemo-and radiotherapy resistance of hypoxic tumors (45).…”
Section: Hif Inhibitorsmentioning
confidence: 99%
“…Thus, no methods are currently available to effectively treat these patients. However, several recent experiments strongly suggest that targeting mitochondria will yield effective strategies to treat lung cancer patients in the future [14][15][16][17][18].…”
Section: Unique Clinical Problems Of Lung Cancermentioning
confidence: 99%
“…Several studies have suggested that inhibiting mitochondrial function makes drug-resistant tumors more sensitive to treatment [14][15][16]18]. When oxidative phosphorylation was suppressed, cancer became less able to proliferate in an anchorage-independent manner [14].…”
Section: Lung Cancer Cells Are Extremely Susceptible To Inhibitors Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…Developed by Bayer (Germany), BAY87-2243 is a potent HIF-1a and HIF-2a inhibitor with antitumour activity. 98 A phase I clinical study conducted to evaluate the MTD of BAY87-2243 in patients with advanced malignancies (ClinicalTrials.org identifier NCT01297530) was terminated due to unanticipated high toxicities.…”
Section: Other Hif-1a Inhibitorsmentioning
confidence: 99%